new species Telipogon (Oncidiinae) from Bolivia - Zárate, Modesto (2026)
Telipogon minutus, from the Carrasco National Park in the Bolivian Yungas, is proposed as a new species. Plants of T. minutus, which reach up to 4 cm in height, are the smallest known Bolivian Telipogon. The new species is characterized by its oblong to ovate labellum, which is weakly sub-auriculate and retuse at the base, with a semi-circular stigma, a column with two lateral lobes and a mammillary protuberance at the apex, and two tufts of setae with trifurcate apices. A description, figures, and a distributional map of the new taxon are provided, along with a discussion of the differences between the new species and morphologically similar Telipogon species.